Gaya Komunikasi Pelatih Dalam Meningkatkan Prestasi Atlet Club Karate Universitas Singaperbangsa Karawang - Nurul, Nurul Aeni; Kusumaningrum, Rastri; Budhiarti, Tri Widya (Jurnal Speed (Sport, Physical Education, Empowerment), 2024)
This research is motivated by the importance of effective communication between coaches and athletes in improving athlete performance, especially at the Karate Club of Singaperbangsa University Karawang. The purpose of this research is to identify and analyze the effectiveness of six different trainer communication styles, namely The Controlling Style, The Equalitarian Style, The Structuring Style, The Friendly Style, The Dramatic Style, and The Impression Leaving Style. The research method used was qualitative with data collection techniques through in-depth interviews with 5 informants consisting of 2 coaches and 3 athletes, as well as direct observation during training sessions and competitions. The research results show that the application of appropriate communication styles by coaches can significantly improve athlete performance. Coaches who use The Controlling Style are able to create a structured and disciplined training environment, while The Equalitarian Style and The Friendly Style increase athlete involvement and motivation. The Structuring Style helps athletes understand achievement targets clearly, while The Dramatic Style and The Impression Leaving Style increase focus and motivation through the use of dramatic expressions and memorable messages. This research found that coaches who are flexible and able to adapt their communication style to the athlete's situation and needs can create a more effective training environment and support holistic athlete development. Keywords: Coach Communication, Athlete Performance, Communication Style, Karate, Sports Training